Peran Guru Dalam Pembelajaran Berdiferensiasi Di Taman Kanak-Kanak ABA Al-Furqon Nitikan - Fatimah, Siti; Mashar, Riana (Pendagogia: Jurnal Pendidikan Dasar, 2023)
The purpose of writing this article is to describe the teacher's role in Differentiated Learning in ABA Al-Furqon Nitikan Kindergarten. This type of research was carried out using descriptive research methods with a qualitative approach. The research was conducted at ABA Nidotan Kindergarten, Yogyakarta City. Data collection techniques are observation, documentation study of teacher learning plans, and unstructured interviews with class teachers. The instruments used were observation instruments, questionnaires, and document analysis guidelines. Data analysis was carried out using qualitative techniques, Milles & Huberman (2010), namely the activities in the analysis include data reduction, data display, and conclusion drawing/verification. Based on the results of the research activities carried out, it can be concluded that: (1) class B-2 students have diverse characteristics both in terms of ability, background and climate of inclusiveness; & (2) in general, teachers have carried out differentiated learning both in terms of educational strategies with differentiated content (content), processes, and products. However, it cannot be maximized due to the limitations that the teacher has in applying differentiated learning.